Analysis of Food Security Situation in Warri, Nigeria - Omojimite, Ben U. (Journal of Social and Development Sciences, 2011)
This study attempts to investigate whether there could be food insecurity incidence in an ‘’oil city’’ of Warri, Nigeria. The paper also examines the determinants of food insecurity among the households studied. The socio-economic characteristics of 260 households were collected by means of a structured questionnaire. A food insecurity index was constructed and was used to assess household food insecurity incidence. The results obtained were analysed by means of tables and percentages and found that on the average the incidence of food insecurity is high in the study area, implying that the benefits of oil and gas activities in Warri do not actually benefit all in the communities studied Also, a logit model was specified and tested to determine the factors that affect food insecurity in the study area. The results of the two approaches used in this study reveal that the age of household heads, sex of household heads, the type of occupation of household heads and dependency ratio all exacerbate food insecurity in the study area. The level of educational attainment of household heads, the nature of occupation of household heads and income of house heads tend to reduce the probability of households being food insecure. The study recommends food aid and food subsidy to the vulnerable in the area. It also recommends expanded educational facilities to enable inhabitants attain higher levels of education.